NILAI-NILAI PENDIDIKAN AL-QURAN SURAT AL FURQON AYAT 63-68 DAN IMPLEMENTASI DALAM PENDIDIKAN AKHLAK DI LINGKUNGAN KELUARGA - Deita Shaumi; Luthfi, Rifyal; Dedi (INTEGRATIF |Jurnal Magister Pendidikan Agama Islam, 2024)
Nowadays, there are many moral crises among students, one of which is bullying cases between students from elementary to high school. One of the internal factors of the moral crisis is the lack of moral education in the family environment. The purpose of this study is to understand the concept of moral education in Islam, the values of moral education in QS. Al-Furqon verses 63-68 and the implementation of moral education values in QS. Al-Furqon verses 63-58 in the family environment. The researcher used a qualitative research approach to find the results of the study. Educating morals through Islamic education aims to create students who have characters based on Islamic religious values. The values of moral education contained in QS. Al-Furqon verses 63-68 are; humble attitude, obedience, khauf, justice, and piety. The implementation of moral education values in QS. Al-Furqon verses 63-68 is carried out through three stages; pre-conventional, conventional and post-conventional. At the preconventional stage, what is considered good to do is what can be physically felt as something good for him. At the conventional stage, what is considered good to do is what gets approval from his friends or people who have authority over him. At the postconventional stage, what is considered good to do is what he himself judges is good to do. Further research can examine the results of this study using quantitative methods or field research